7. Using identities, simplify the following: (2) i) (x + 3 ) (x + 1)​

Question

7. Using identities, simplify the following: (2)
i) (x + 3 ) (x + 1)​

in progress 0
Arya 1 month 2021-09-14T23:04:33+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-14T23:05:49+00:00

     \star \star \star \star \star \star \star \star \star

    Identity

    ( x + a ) ( x + b ) = (x) ^(2) + (a + b ) x + a b

    ◆ x = x

    ◆ a = 3

    ◆ b = 1

    ==> ( x + 3 ) ( x + 1 ) = x ^ 2 + ( 3 + 1 ) x + ( 3 × 1 )

    Answer ==

    ( x + 3 ) ( x + 1 ) = x ^ 2 + 4 x + 3

    I hope this will help you...

    0
    2021-09-14T23:06:30+00:00

     \large \red{ \underline{ \underline{ \green{ \rm \: solution : }}}}

    \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \rightarrowIdentity:

    \bigstar (x + a)(x + b) = x² + (a + b)x + ab

    here,

    • x = x
    • a = 3
    • b = 1

    \implies (x + 3 ) (x + 1) = x² + (3 + 1)x + (3×1)

    \implies \orange{ \boxed{ \underline{ \purple{ \rm \:  (x + 3 ) (x + 1) = x² + 4x + 3}}}}

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )